PERLINDUNGAN HUKUM PEMULIA VARIETAS JAGUNG TALENTA ATAS PEREDARAN TANPA HAK BENIH OLEH PETANI KONTRAK MENURUT UNDANG-UNDANG NO 29 TAHUN 2000 TENTANG PERLINDUNGAN VARIETAS TANAMAN: Talented Corn Variety Breeders Over The Unrighted Distribution Seeds By Contract Farmers According Law Concerning Protection Plant Varieties - Apriandi Dardika; Simona Bustani (Faculty of Law, Universitas Trisakti, 2024)
(E) Plant Variety Protection Rights are special rights granted by the state to breeders and/or Protection of Plant Varieties rights holders to use their own varieties resulting from their breeding or to give approval to other people or legal entities to use them for a certain time. The main problem in this case is how legal protection is for corn plant breeders who produce the Talenta corn variety according to Law number 29 of 2000 on Protection of Plant Varieties and how the government is trying to prevent violations of breeders' rights. This research uses descriptive normative legal research methods, the type of data uses secondary data and is studied qualitatively, so that way of drawing conclusions uses deductive logic. The results and conclusions are Law number 29 of 2000 on Protection of Plant Varieties is adequate to protect breeders both from its articles and the implementation of law enforcement. Farmers do not yet understand what legal restrictions there are in implementing contracts, so the challenge lies in monitoring and controlling the use of plant varieties. Collaboration between plant breeders, government, related institutions, and the seed industry is key to maintaining the success of PVP systems.